Influence of different types of light curing units and photoinitiators in microhardness and color of composite resins after immersion in wine - Morganna Borges de Almeida Souza; André Luiz Fraga Briso; Fernanda de Souza e Silva Ramos; Bruna de Oliveira Reis; Paulo Henrique dos Santos; Ticiane Cestari Fagundes (Brazilian Dental Science)
Abstract